Synthesis, characterization, powder X-ray diffraction analysis, thermal stability, antioxidant properties and enzyme inhibitions of M(II)-Schiff base ligand complexes - Buldurun, Kenan; Turan, Nevin; Bursal, Ercan; Aras, Abdulmelik; Mantarci, Asim; Colak, Naki; Turkan, Fikret (Taylor & Francis Inc, 2020)
The Schiff base ligand ((E)-6-methyl-2-(2,3,4-trimethoxybenzylideneamino)-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carbonitrile) and its cobalt(II) and palladium(II) complexes were successfully prepared. The structure of the compounds was elucidated by various techniques (NMR, FT-IR, powder X-ray diffraction, microanalysis, TGA, magnetic susceptibility, mass spectrometry). The Pd(II) complex showed a square planar geometry and the Co(II) complex had an octahedral geometry. ABTS (2,2-azino-bis 3-ethylbenzothiazloine-6-sulphonic acid), DPPH (1,1-diphenyl-2-picrylhydrazyl), FRAP (ferric-reducing antioxidant power) and CUPRAC (cupric reducing antioxidant capacity)in vitromethods were applied to identify the antioxidant features of the synthesized compounds. In addition, glutathione S-transferase and acetyl/butyryl cholinesterase enzymes were examined for possible inhibition capacities of the complexes. According to the enzyme activity measurements, Ru(II) complex inhibited both GST and BChE enzymes, while Fe(II) complex inhibited only AChE enzyme. Furthermore, the antioxidant activities and enzyme inhibitions of the previously synthesized Fe(II) and Ru(II) complexes of the same ligand were examined to make a comparison of the metal complexes. Communicated by Ramaswamy H. Sarma
Mantarci, Asim/0000-0001-8369-3559; Turan, Nevin/0000-0001-6740-6812; Gulcin, ilhami/0000-0001-5993-1668; BULDURUN, Kenan/0000-0002-2462-7006
Keywords: Metal complex; Schiff base; spectroscopic techniques; antioxidant activity; enzyme inhibition